Difusão de Informação em Redes Sociais: um modelo de recomendação no contexto educacional - Neves, Felipe; Ströele, Victor; Campos, Fernanda (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Recommender Systems (RS) seek to present resources with features that meet users' interest and needs. The use of these systems with social networks, which have characteristics of information propagation and sharing, enables the dissemination of recommended resources. In order to study and identify the information diffusion metrics that are most related to social networks, this article presents an architecture, with the purpose of recommending educational resources to diffusing people, increasing the social network reach. The proposal was evaluated through a feasibility study and a case study in an educational context on the Twitter social network. The results point to the feasibility of the proposal, not restricted to its validation context.